Espaço urbano e pobreza: A alma encantadora das ruas e Na pior em Paris e Londres - Tiago de Holanda Padilha Vieira (2017)
This thesis analyses how urban space and poverty are shaped by the character narrators of two works: A alma encantadora das ruas (1908), a collection of crônicas written by João do Rio, and George Orwells semi-diary Down and out in Paris and London (1933). Our main hypothesis is that those narrators and their own bodies, by moving through broken cities, perform and propose spatial practices based on a kind of non-hierarchical, mutually illuminating encounter between different positions. Therefore, the books elaborate fundamentally similar projects, but each with singularities that we investigate. Among these peculiarities, we are primarily concerned with the ways the narrators vary their perspectives and thus present distinct proposals for approaching and moving away from poverty. The notions of encounter and (social) space are considered as parts of a theoretical set drawn by Henri Lefebvre, the author with wich we mainly dialogue in order to theoretically understand the spacial organization as an endless political production, as a field of disputes between forces, representations, practices, symbols, images. The other main theoretical references of this thesis are Michel de Certeaus study on everyday life especially his formulation of tactics, important to discuss the political meanings of the practices of the narrators and poor characters, who fluctuate between attitudes of submission and (at least potential) threat to the commands of dominant political-economic orders and Walter Benjamins studies on eighteenth century Paris and on Baudelaires works mainly the notions of schock and of two kinds of experience (Erlebnis and Erfahrung), by means of which we point to a certain predominance of the present time that subdues the poors everyday life, more clearly in Orwells work. Although we do not intend to carry out a comparative study of the two books, we hope that the combined inquiry of both can enrich their interpretations.